Bridging The Gap: Collaborative Governance In Education For Ex-Leprosy Children – A Case Study In Tanjungkenongo 2 Elementary School, Indonesia - Hidayat, Endik; Izzudin Baihaqi, Aufa; Anisykurlillah, Rosyidatuzzahro (International Journal of Educational Research & Social Sciences, 2023)
The background of this study is the phenomenon of collaboration among state actors and non-governmental actors in the implementation of primary level education for children of former lepers of Sumberglagah. The location of this study is aroung the Tanjungkenongo 2 State Elementary School. This study aims to answer two questions: how to identify the actors of collaborative governancebased education in Sumberglagah elementary school and what are the dynamics of collaboration among the actors in implementing primary education in the Sumberglagah leprosy village? It applied qualitative methods and case study research due to the uniqueness of Sumberglagah leprosy village, This study discovered that the educational process of SD Tanjungkenongo 2 has involved several actors: East Java provincial government, Mojokerto Regency government, Tanjungkenongo village government, school principals and teachers at SD Tanjungkenongo, Ministry of Education and Culture through campus teaching programs and communities around Sumberglagah. The actors' collaborative relationship runs dynamically based on three values; for instances consensus orientation in decision making, multi-stakeholder communication in social relations and bureaucracy, and various resources in achieving common goals.